Proxy voting and the SEC - Pound, John (Journal of Financial Economics, 1991)
This paper analyzes the SEC's proxy regulations and assesses their effects on corporate governance. The proxy rules began in 1935 as a minimal series of disclosure requirements and a prohibition against fraud. By 1956, they imposed extensive and wide-ranging disclosure requirements on anyone wishing to communicate about voting issues and required that all such communications be cleared in advance — in essence, censored — by the SEC. I present evidence that since that time, the rules have significantly increased the costs of communication and coordinated action among shareholders. They have thus deterred shareholder initiatives and inhibited the development of a private market for information about voting issues.